The Role of Special Educators in Dealing with Students' Learning Difficulties/Qualitative Study Exploring the Parents' Experience on the Work of Special Educators with Their Children's Learning Difficulties - Kaouki Maria-Anastasia; Lamproukou Markella (2018)
Abstract, Introduction, Preamble, Chapter Outline, Literature Review, Introduction, Learning Difficulties (LD), Categories of LD, Special Educators, Types of Intervention for Children and Families, Aims and Purposes of the Present Research, Metodology, Introduction, Data Collection, Participants, Materials, Analytic Strategy, Procedure, Ethics, Analysis of the Findings, The Research Findings, Child Difficulties Before the Diagnosis, Behaviour Problems, Diagnosis, Information on Parents Related to Learning Difficulties, The Role of Teachers and Special Educators, Parents' Expectations in Relation to the Role of the Special Educator, Discussion, Connecting Themes Back to the Literature, Further Reflections, Implications and Recommendations for Research Arising from This Study, Limitations of the Study, Conclusion, References, Appendices.